(untitled) (Pulse, 2014)
Objectives Aim of the study was to evaluate the primary in-hospital success and 90 days outcome of PCI in patients with CTO lesions, using either Bare-metal stents (BMS) or Drug Eluting Stent (DES) like Sirolimus-eluting or Paclitaxel-eluting stent. Methods Total 71 patients were included in this non-randomized prospective cohort as per the definition of CTO, from a total of 875 patients who had PCI at our center in the quantifying period. Total 92 stents were deployed in 71 patients. After the guide wire crossing and the balloon dilation, measurement of the culprit lesion were done by using Siemens QCA measuring system. Among the patients, Male: 59 and Female: 12. Mean age were for Male: 53yrs, for Female: 65yrs. Associated CAD risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking (all male). Results Our study shows 71 patients (8.1%) had CTO lesion out of total 875 PCI procedures. Among the study group; 56 (79%) were Dyslipidemic, 50 (70%) were hypertensive: 40 (56%) patients were Diabetic, 25 (42%) were all male smoker. Female patients were more obese (BMI M 26: F 27) and developed CAD in advance age. We found that the incidences of CTO lesions were more in LAD territory 27 (38%) followed by RCA 26 (37%) and LCX 18 (25%). Average length and diameter of stented vessel was greater in RCA than LAD and LCX. Stents used: BMS 34 (36.9%), Sirolimus 25 (27.2%), Paclitaxel 18 (19.6%), Biolimus 10 (10.8%) and Everolimus 5 (5.4%). Post procedural, in-hospital and 90 days out come was 100% in our present study. Conclusion Our study has revealed that PCI in patients with CTO lesion has shown good success rate in our hospital with no procedural complication both in-hospital and 90 days after, either treated with BMS or DES. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20185 Pulse Vol.5 January 2011 p.19-26